2021
DOI: 10.1001/jama.2021.15703
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moderate vs Mild Therapeutic Hypothermia on Mortality and Neurologic Outcomes in Comatose Survivors of Out-of-Hospital Cardiac Arrest

Abstract: IMPORTANCEComatose survivors of out-of-hospital cardiac arrest experience high rates of death and severe neurologic injury. Current guidelines recommend targeted temperature management at 32 °C to 36 °C for 24 hours. However, small studies suggest a potential benefit of targeting lower body temperatures.OBJECTIVE To determine whether moderate hypothermia (31 °C), compared with mild hypothermia (34 °C), improves clinical outcomes in comatose survivors of out-of-hospital cardiac arrest.DESIGN, SETTING, AND PARTI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 29 publications
(30 reference statements)
2
14
0
Order By: Relevance
“…Similar results were reported in the CAPITAL CHILL (Effect of Moderate vs Mild Therapeutic Hypothermia on Mortality and Neurologic Outcomes in Comatose Survivors of Out-of-Hospital Cardiac Arrest: The CAPITAL CHILL Randomized Clinical Trial) trial [ 41 ], published shortly after the TTM2 trial. This was a single-center, double-blinded, randomized, clinical superiority trial carried out in a tertiary cardiac care center in eastern Ontario, Canada.…”
Section: Novel Approaches To Targeted Temperature Managementsupporting
confidence: 81%
“…Similar results were reported in the CAPITAL CHILL (Effect of Moderate vs Mild Therapeutic Hypothermia on Mortality and Neurologic Outcomes in Comatose Survivors of Out-of-Hospital Cardiac Arrest: The CAPITAL CHILL Randomized Clinical Trial) trial [ 41 ], published shortly after the TTM2 trial. This was a single-center, double-blinded, randomized, clinical superiority trial carried out in a tertiary cardiac care center in eastern Ontario, Canada.…”
Section: Novel Approaches To Targeted Temperature Managementsupporting
confidence: 81%
“…The trial randomly assigned adult patients to a targeted temperature of 31 °C or 34 °C for 24 h, and demonstrated that a lower temperature goal of 31 °C did not improve outcomes compared to the standard of care targeted temperature of 34 °C. It is important to note that this was a single-center study and likely underpowered [ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“… 30 The primary outcome of 6-month all-cause mortality was no different between the groups. In the CAPITA-CHILL study (single-centre, double-blind randomized clinical superiority trial), 389 patients with OHCA were randomly assigned to 31°C (193 patients) vs. 24°C (196 patients) for 24 h. 31 Primary outcome was 180-day all-cause mortality/poor neurological outcome with no difference between the groups. These findings support recommendations in current resuscitation guidelines.…”
Section: Resuscitation Sciencementioning
confidence: 99%